Little Owls Night - Srinivasan, Divya (New York : Viking, an imprint of Penguin Young Readers Group, 2013)
Little Owl enjoys a lovely night in the forest visiting his friend the raccoon, listening to the frogs croak and the crickets chirp, and watching the fog that hovers overhead.
Accelerated Reader
Keywords: Owls -- Juvenile fiction; Night -- Juvenile fiction; Forests and forestry -- Juvenile fiction; Forest animals -- Juvenile fiction; Owls -- Fiction; Night -- Fiction; Forests and forestry -- Fiction; Forest animals -- Fiction